Changes in Endosymbiont Complexity Drive Host-Level Compensatory Adaptations in Cicadas - Matthew A. Campbell (American Society for Microbiology, 2018)
ABSTRACT For insects that depend on one or more bacterial endosymbionts for survival, it is critical that these bacteria are faithfully transmitted between insect generations. Cicadas harbor two essential bacterial endosymbionts, “Candidatus Sulcia muelleri” and “Candidatus Hodgkinia cicadicola.” In some cicada species, Hodgkinia has fragmented into multiple distinct but interdependent cellular and genomic lineages that can differ in abundance by more than two orders of magnitude. This complexity presents a potential problem for the host cicada, because low-abundance but essential Hodgkinia lineages risk being lost during the symbiont transmission bottleneck from mother to egg. Here we show that all cicada eggs seem to receive the full complement of Hodgkinia lineages, and that in cicadas with more complex Hodgkinia this outcome is achieved by increasing the number of Hodgkinia cells transmitted by up to 6-fold. We further show that cicada species with varying Hodgkinia complexity do not visibly alter their transmission mechanism at the resolution of cell biological structures. Together these data suggest that a major cicada adaptation to changes in endosymbiont complexity is an increase in the number of Hodgkinia cells transmitted to each egg. We hypothesize that the requirement to increase the symbiont titer is one of the costs associated with Hodgkinia fragmentation. IMPORTANCE Sap-feeding insects critically rely on one or more bacteria or fungi to provide essential nutrients that are not available at sufficient levels in their diets. These microbes are passed between insect generations when the mother places a small packet of microbes into each of her eggs before it is laid. We have previously described an unusual lineage fragmentation process in a nutritional endosymbiotic bacterium of cicadas called Hodgkinia. In some cicadas, a single Hodgkinia lineage has split into numerous related lineages, each performing a subset of original function and therefore each required for normal host function. Here we test how this splitting process affects symbiont transmission to eggs. We find that cicadas dramatically increase the titer of Hodgkinia cells passed to each egg in response to lineage fragmentation, and we hypothesize that this increase in bacterial cell count is one of the major costs associated with endosymbiont fragmentation.